Epidemiology of Plum pox virus in Japanese plums in Spain - Cambra, Mariano; Gorris, María T.; Capote, Nieves; Asensio, M.; Martínez, M. Carmen; Bertolini, Edson; Collado, C.; Hermoso-De-Mendoza, Alfonso; Mataix-Gato, Emilio; Lopez, A. (2017)
The Japanese plum (Prunus salicina) industry is economically important in Spain and in other countries with Mediterranean climate. P. salicina was described as a natural host of Plum pox virus (PPV) in Spain in 1984, where the ‘Red Beaut’ cultivar become an important source of inoculum and it spread the virus to apricots and plums along the Spanish Mediterranean coast. The spatial and temporal spread of PPV was monitored along a twelve year period in a collection of 41 Japanese plum cultivars, planted in Luchente (Valencia) in 1990. PPV incidence in 1991 was 11% and reached 95% after 13 years. The spread of the virus followed a logistic model without aggregation of the new infected trees around the previously infected ones. In May of 1992, 2002 and 2003 the numbers of aphid species landing on mature Japanese plum trees were estimated by counting the number of shoots (average of different cultivars: 752) and aphids trapped on “sticky shoots”. The proportions of the different aphid species captured were: Aphis spiraecola (43%), A. gossypii (18%), Hyalopterus pruni (6%), Brachycaudus prunicola (6%), A. craccivora (3%) and Myzus persicae (2%), and other species (22%). Vigorous Japanese plum cultivars were the most visited with 5,606 aphids landing in May/tree. An average of 667 PPV-viruliferous aphids visited each vigorous Japanese plum tree in May. The percentage of detection of viral RNA in the aphid species that landed was 11.9%. This high incidence of viruliferous aphids is consistent with the high incidence and rapid spread of PPV in Japanese plums in the region. A complete serological and molecular characterisation of the PPV isolates spreading in P. salicina in Spain showed that only PPV-D was present. Seven different serogroups and variability in the nucleotide sequence of the NIb and CP genes were found among 21 PPV isolates studied. Pre-inoculation of trees with a typical PPV-D isolate did not cross-protect Japanese plums against the infection with PPV-M inoculated by grafting. The sensitivity to PPV-D of 33 Japanese plum cultivars was evaluated. Unmarketable fruits from infected trees reached as maximum as 15%, making possible economic profit in heavily infected plantations.